2020
DOI: 10.1080/15538362.2020.1769526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Essential Oils to Control Penicillium Sp. In In Vitro and in In Vivo on Grapevine (Vitis Vinifera L.) Fruit

Abstract: The expansion of natural crop protection products as alternatives to the use of synthetic fungicides is currently popular. In this project the effects of essential oils to control Penicillium sp. in vitro and in vivo on grapevine (Vitis vinifera L.) fruit. In the present study, the inhibitory effects of anise, chamomile, black caraway, and marjoram essential oils against Penicillium sp. tested at various concentrations (0, 200, 400, 600, and 800 μL L −1 ) in vitro and in vivo. The in vitro results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…11 Recent studies have demonstrated the use of EOs as biocontrol agents against postharvest spoilage or pathogenic fungi. 12,13 Jahani et al 12 investigated the inhibitory effects of anise, black caraway, chamomile, and marjoram EOs at different concentrations (0, 200, 400, 600, and 800 μl/L) against Penicillium sp. in vitro, and in vivo using grapevine (Vitis vinifera L.) fruit.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Recent studies have demonstrated the use of EOs as biocontrol agents against postharvest spoilage or pathogenic fungi. 12,13 Jahani et al 12 investigated the inhibitory effects of anise, black caraway, chamomile, and marjoram EOs at different concentrations (0, 200, 400, 600, and 800 μl/L) against Penicillium sp. in vitro, and in vivo using grapevine (Vitis vinifera L.) fruit.…”
Section: Introductionmentioning
confidence: 99%
“…growth was totally repressed by anise EO treatment at 800 μl/L. 12 Nikkhah et al 13 characterised the volatile composition of marjoram, cinnamon, rosemary, and thyme EOs, and investigated their possible antifungal synergistic effects in double and triple combinations against P. expansum and B. cinerea. Triple combination of thyme, cinnamon and rosemary had synergistic effect against P. expansum and B. cinerea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation